Sustainable Natural Solar Drying of Microbreweries Spent Grains: A Comparison with Common Electric Convective Drying. Issue 1 (1st January 2022) - Fabani, MP; Capossio, JP; Reyes-Urrutia, A; Rodriguez, R; Mazza, G
Abstract: In recent years, local microbreweries are increasingly capturing the consumer's interest with a wide range of different types of beer. Because of the insertion of microbreweries scattered around the country, large amounts of spent grains have been made available locally to be used, for instance, as animal feed. However, those spent grains, which are mainly formed by malting barley (or malt), are materials suitable for further valorization. Turning the spent grains from waste to a raw material that can be later used to produce non-traditional flour requires a thermal treatment, i.e. a drying process. A natural convection solar dryer (NCSD) was evaluated as an alternative to a conventional convective electric drying system for the dehydration process of local microbrewer's spent grains. Two types of breweries' spent grains-BSG-(Golden Ale and Red Ale) were dried at different daytime hours. Sustainability indexes, Specific Energy Consumption (SEC), and CO2 emissions of the conventional dryer were calculated and used to determine the environmental benefits and drawbacks of the NCSD.